Nusinersen Administration Via an Intrathecal Port in a 16-Year-Old Spinal Muscular Atrophy Patient with Profound Scoliosis - Flotats-Bastardas, Marina; Linsler, Stefan; Zemlin, Michael; Meyer, Sascha (Pediatric Neurosurgery, 2020)
Introduction: Spinal muscular atrophy (SMA) is a genetic disease affecting the second motor neuron, causing progressive muscle atrophy and weakness due to decreased expression of the survival motor neuron. Different subtypes exist, type 2 being one of the most frequent ones. These patients show a high incidence of scoliosis requiring surgery. In 2016 and 2017, the Federal Drug Administration and European Medical Agency approved nusinersen for all types of SMA. It is a splicing modifier that enhances the expression of survival motor neuron and it has to be administered intrathecally. In patients with profound scoliosis, intrathecal administration can be challenging. Here, we present our experience with the implantation of an intrathecal port in a patient with SMA type 2. Case Presentation: A 16-year-old girl with SMA type 2 was referred for intrathecal nusinersen therapy. Because of severe scoliosis, spondylodesis of the segments TH7-S1 was performed at 14 years of age. The first two loading doses were given by spinal tap under sedation and computed tomography guidance, but we were unable to administer the following dose because of severe scoliotic spinal deformation. To ensure further drug therapy, an intrathecal port catheter (Celsite® Safety; Braun, Germany) was implanted via microsurgical hemilaminectomy L4. Further intrathecal nusinersen administration was uneventful. Conclusion: We conclude that the implantation of an intrathecal port system in patients with SMA and profound scoliosis is a safe and feasible procedure and allows the administration of nusi-nersen while reducing the need for sedation and exposure to radiation.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Inthrathecal port; Nusinersen; Scoliosis; Spinal muscular atrophy